Mass Communication Through Digital Media (Trinity Journal of Management, IT & Media (TJMITM), 2016)
We reside in a media-saturated world and rely on a kind of historic  and new media for understanding, amusement, and connection.  The beginnings of mass media and mass communication go  back around 500 years to the “print revolution” that came about  in Europe in the fifteenth century. As we improved by means of  the centuries, mass verbal exchange evolved from a mechanical  system to digital transmissions, which lead the way for the  digitized world of at present. Whilst technological advances are  an foremost a part of the narrative involving media, the effects of  media are also major to don’t forget. On this chapter, we can speak  about some functions and theories of mass conversation and some  of the key moral problems concerning media and conversation.
Keywords: Digital Media; print revolution; mass verbal exchange